Peran Notaris dalam Perlindungan Hak Kekayaan Intelektual: Studi Komparatif Praktik Hukum Indonesia dan Standar Internasional - Damaiyanti, Alifia; Roisah, Kholis (LPPM Universitas Ekasakti Padang, 2024)
This study explores the role of notaries in the protection of intellectual property rights (IPR) in Indonesia compared to international standards, aiming to identify opportunities for improvement and harmonization. Employing qualitative research methods and comparative studies, the research combines literature analysis, comparative analysis, and methodologies of content analysis and SWOT. Findings reveal significant differences in the practices of Indonesian notaries compared to international standards, facing challenges such as regulatory complexity, technological dynamics, and limited IPR awareness. It is recommended that Indonesia aligns its IPR regulations with international standards, enhances notary training, adopts advanced technology, and strengthens inter-agency cooperation. These steps are expected to improve IPR protection, reinforce Indonesia's position in the global economy, and support a sustainable ecosystem of innovation and creativity.